Random amplified polymorphic DNA technique for detection of plant based adul- terants in chilli powder (Capsicum annuum) - B Sasikumar, K Dhanya, S Syamkumar, K Jaleel, (Journal of Spices and Aromatic Crops, 2008)
The present study reports a modified protocol for isolation of good quality DNA from chillipowder and its probable adulterants (dried red beet pulp, almond shell dust and powderedZiziphus nummularia fruits) and the utility of RAPD primers for detection of adulterants inmarketed chilli powder. Selected RAPD primers, which produced adulterant specific bands insimulated samples were used for analyzing market samples of chilli powder. Out of the sixmarket samples analyzed, one sample amplified Z. nummularia specific band indicating theoccurrence of adulteration in market samples. All the market samples tested were free fromdried red beet pulp or almond dust adulteration.